2018
DOI: 10.5005/jp-journals-10048-0046
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Comparison of the Marginal Adaptation of an Epoxy, Calcium Hydroxide-based, and Bioceramic-based Root Canal Sealer to Root Dentin by SEM Analysis: An In Vitro Study

Abstract: Aim:The aim of this study is to evaluate and compare the sealer penetrability and gap formation of root canal sealer to root dentin filled with AH Plus, Sealapex, and BioRoot RCS. Materials and methods: Twenty-seven mandibular second premolars were selected and were radiographed at two angulations. The teeth were stored in labeled plastic vials containing artificial saliva and were randomly assigned to three groups based on the sealer, group I-AH Plus (n = 9), group II-Sealapex (n = 9), and group III-BioRoot R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In addition to solubility, the chemical composition of hydraulic calcium silicate cements also plays a crucial role in tubular penetration. Hydrophilic materials tend to penetrate dentinal tubules more deeply than hydrophobic materials [17]. Studies have shown that hydraulic calcium silicate cements exhibit superior marginal adaptation when compared to epoxy resin-based materials, attributed to the small particle size of hydraulic calcium silicate cement materials, facilitating enhanced penetration through dentinal tubules [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to solubility, the chemical composition of hydraulic calcium silicate cements also plays a crucial role in tubular penetration. Hydrophilic materials tend to penetrate dentinal tubules more deeply than hydrophobic materials [17]. Studies have shown that hydraulic calcium silicate cements exhibit superior marginal adaptation when compared to epoxy resin-based materials, attributed to the small particle size of hydraulic calcium silicate cement materials, facilitating enhanced penetration through dentinal tubules [18].…”
Section: Discussionmentioning
confidence: 99%
“…The materials employed in this clinical procedure should possess the ability to consistently provide sealing, exhibit good biocompatibility, ensure effective adhesion to root canal walls and maintain dimensional stability. Additionally, it is imperative for these materials to be hydrophilic [17,18], with a low solubility, be easy to handle and have a short setting time and good radiopacity [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The comparable result of ADSEAL to One-Fil may be related to the capability of resin sealer to react with any exposed amino groups in collagen and create covalent bonds after the epoxide ring of resin is opened (Kebudi Benezra et al, 2018). The mechanism of bonding of hydraulic calcium silicate sealer to root dentin could be linked to the following mechanisms; infiltration of the sealer's mineral content into the intratubular dentin resulting in the establishment of a mineral infiltration zone produced after denaturing the collagen fibers with a strong alkaline sealer, Partial reaction of calcium silicate hydrogel with phosphate in a moistened environment leading to the formation of hydroxyapatite with the dentin substrate, and Diffusion of the sealer particles into the dentinal tubules to produce mechanical interlocking bonds added to the chemical bond (Mathew et al, 2019) The results of this study coincide with other studies that found no significant difference between pre-mixed TotallFill biocermic sealer (FKG, Switzerland) and AH Plus resin sealer (DENTSPLY, USA) as both sealers exhibited similar bonding strength to the root canal (Gyulbenkiyan et al, 2020). Also, other studies came up with the same conclusion while investigating the premixed TotallFill, relating their results to the small size particle, followability and expansion of the premixed bioceramic sealer allowing it to penetrate into the dentinal tubules while AH Plus sealer is mild acidic pH which could etch dentin slightly, thereby improving sealer dentin adaptation (Salem et al, 2019).…”
Section: Discussionmentioning
confidence: 99%